Cognitive Screening of Adults With Postlingual Hearing Loss: A Systematic Review. (21st July 2020) - Raymond, Mallory; Barrett, Devon; Lee, Daniel Juno; Peterson, Shenita; Raol, Nikhila; Vivas, Esther X.
Abstract : Objective: To systematically review the evidence for the use of cognitive screening tools for adults with postlingual hearing loss. Data Sources: PubMed, Embase, Scopus, PsycINFO (EBSCO), CINAHL (EBSCO), and CENTRAL (Cochrane Library) electronic databases were searched from inception until October 4, 2018. Review Methods: Articles were reviewed for inclusion by 2 independent reviewers. The references of included articles were hand‐searched for additional relevant articles. Data were extracted by 2 independent extractors. Results: Of 2092 articles imported from the search, 81 were included for the review. Nearly a third (31%, n = 25) included patients with profound hearing loss. In total, 23 unique tools were used for 105 unique applications. The Mini Mental Status Exam (MMSE) was the most commonly used (54%, n = 55), followed by the Montreal Cognitive Assessment (MoCA) (19%, n = 10). Nearly half of the tools were used to define patient inclusion or exclusion in a study (48%, n = 50), followed by examination of a change after an intervention (26%, n = 27). Two articles attempted to study the validity of the MMSE and MoCA for screening patients with mild to moderate hearing loss and found mixed effects of the auditory components. There were no validation studies identified from the search. Conclusion: Many different cognitive screening tools have been used to study patients with postlingual hearing loss. The effects of the auditory components of these tools may be deleterious but ultimately remain unclear from the available evidence. To date, there has been no validation of any cognitive screening tool to be used for adults with postlingual hearing loss.